Prevalence and correlates of suspected dementia in older adults receiving primary healthcare in Wuhan, China: A multicenter cross-sectional survey - Wang, Zong-Qin; Fei, Lei; Xu, Yan-Min; Deng, Fang; Zhong, Bao-Liang (Frontiers in Public Health, 2022)
Background: Integrating the management of dementia into primary healthcare is a cost-effective way to reduce the burden of dementia but the clinical epidemiology of dementia in primary healthcare settings remains unclear. This study investigated the prevalence and correlates of suspected dementia in Chinese older adults receiving primary healthcare. Methods: In this multicenter cross-sectional survey, a total of 773 older adults (≥65 years) were consecutively recruited from seven urban and six rural primary care clinics in Wuhan, China, and interviewed with the validated Chinese version of the Brief Community Screening Instrument for Dementia (BCSI-D). Participants with suspected dementia were those who were screened positive on the BCSI-D. Results: The prevalence of suspected dementia in older primary healthcare adults was 26.8%. Factors significantly associated with suspected dementia were female sex (OR=1.95, P<0.001), age-group of 75+ (OR=1.68, P=0.004), poor financial status (OR=4.79, P<0.001), rural residence (OR=1.47, P=0.032), no regular physical exercise (OR=1.74, P=0.002), and stroke and other cerebrovascular diseases (OR=1.97, P=0.015). Conclusions: Chinese older adults receiving primary healthcare are at high risk of suspected dementia. Screening and intervention efforts for dementia in primary healthcare settings may be more useful to target older adults who are women, are 75 years and above, have poor economic status, are rural residents, have no exercise habit, and suffer from cerebrovascular diseases.